Case Report: The impact of severe cryptosporidiosis on the gut microbiota of a pediatric patient with CD40L immunodeficiency - Piazzesi, Antonia; Pane, Stefania; Russo, Alessandra; Del Chierico, Federica; Francalanci, Paola; Cotugno, Nicola; Rossi, Paolo; Locatelli, Franco; Palma, Paolo; Putignani, Lorenza (Frontiers in Cellular and Infection Microbiology, 2023)
Cryptosporidium parvum is a protozoan parasite and one of the leading causes of gastroenteritis in the world, primarily affecting very young children and immunocompromised patients. While infection is usually self-limiting, it can become chronic and even lethal in these vulnerable populations, in whom Cryptosporidium treatments are generally ineffective, due to their acting in concert with a functioning immune system. Here, we describe a case of chronic cryptosporidiosis in a European child with severe CD40L immunodeficiency infected with Cryptosporidium parvum of the IIa20G1 subgenotype, a lineage which has thus far only ever been described in the Middle East. After years of on-off treatment with conventional and non-conventional anti-parasitic drugs failed to clear parasitosis, we performed targeted metagenomics to observe the bacterial composition of the patient’s gut microbiota (GM), and to evaluate fecal microbiota transplantation (FMT) as a potential treatment option. We found that C. parvum infection led to significant shifts in GM bacterial composition in our patient, with consequent shifts in predicted intestinal functional signatures consistent with a state of persistent inflammation. This, combined with the patient’s poor prognosis and increasing parasitic burden despite many rounds of anti-parasitic drug treatments, made the patient a potential candidate for an experimental FMT procedure. Unfortunately, given the many comorbidities that were precipitated by the patient’s immunodeficiency and chronic C. parvum infection, FMT was postponed in favor of more urgently necessary liver and bone marrow transplants. Tragically, after the first liver transplant failed, the patient lost his life before undergoing FMT and a second liver transplant. With this case report, we present the first description of how cryptosporidiosis can shape the gut microbiota of a pediatric patient with severe immunodeficiency. Finally, we discuss how both our results and the current scientific literature suggest that GM modulations, either by probiotics or FMT, can become novel treatment options for chronic Cryptosporidium infection and its consequent complications, especially in those patients who do not respond to the currently available anti-parasitic therapies.